1996
DOI: 10.1159/000201341
|View full text |Cite
|
Sign up to set email alerts
|

Diethyldithiocarbamate, a Superoxide Dismutase Inhibitor, Reduces Indomethacin-lnduced Gastric Lesions in Rats

Abstract: We examined the effect of diethyldithiocarbamate (DDC), the superoxide dismutase (SOD) inhibitor, on the development of gastric lesions induced by indomethacin in rats. Indomethacin (25 mg/kg) was given subcutaneously, and gastric acid secretion, motility, lipid peroxidation, vascular permeability, and myeloperoxidase as well as gastric lesions were measured. Indomethacin produced high-amplitude contractions of the stomach and caused hemorrhagic lesions in the corpus mucosa with significant increase in neutrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 22 publications
1
30
0
Order By: Relevance
“…SBP and heart rate were measured 1 h after oral administration of FA using the tail-cuff method. The dosage of atropine was the same as those reported previously (36,37).…”
Section: Combined Effects Of Fa and Drugs On Blood Pressure In Shrmentioning
confidence: 99%
“…SBP and heart rate were measured 1 h after oral administration of FA using the tail-cuff method. The dosage of atropine was the same as those reported previously (36,37).…”
Section: Combined Effects Of Fa and Drugs On Blood Pressure In Shrmentioning
confidence: 99%
“…The mechanism of NSAIDinduced gastric damage is generally believed to be related to the ability of these agents to inhibit gastric prostaglandin generation (1). However, evidence has been recently produced that leukocyte adherence to the vascu-lar endothelium (2)(3)(4), microcirculatory disturbances, superoxide radicals and protease liberation may be relevant pathogenic mechanisms in NSAID gastropathy (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that NSAIDs are associated with altered gastroduodenal motility (6)(7)(8)(9)(10). Some data indicate that the administration of NSAIDs is followed by either increased gastric contractility, which correlates with gastric damage (6-9) or decreased intestinal spiking amplitude and disruption of migrating motor complexes (10), with no correlation with gastric damage.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main side effect of NSAIDs is gastric injury, the mechanism of which is generally believed to be related to the ability of these agents to inhibit gastric prostaglandin (PG) generation (34). However, recently published evidence suggests that leukocyte adherence to the vascular endothelium (35), microcirculatory disturbances, superoxide radicals, and protease release play a relevant pathogenic role in NSAIDinduced gastropathy (36). In the present study, hind limb rIPC significantly reduced mucosal lesions and neutrophil infiltration in INDO-induced gastric injury in rats.…”
Section: Discussionmentioning
confidence: 99%